Logarithm of short-time Fourier transform for extending the seismic bandwidth - Sajid, M. (Blackwell Publishing Ltd, 2014)
Improving seismic resolution is essential for obtaining more detailed structural and stratigraphic information. We present a new algorithm to increase seismic resolution with a minimum of user-defined parameters. The algorithm inherits useful properties of both the short-time Fourier transform and the cepstrum to smooth and broaden the frequency spectrum at each translation of the spectral decomposing window. The key idea is to replace the amplitude spectrum with its logarithm in each window of the short-time Fourier transform. We describe the mathematical formulation of the algorithm and its testing on synthetic and real seismic data to obtain broader frequency spectra and thus enhance the seismic resolution. Â© 2014 European Association of Geoscientists & Engineers.